2006
DOI: 10.1016/j.ejcts.2006.01.020
|View full text |Cite
|
Sign up to set email alerts
|

The UW solution has greater potential for longer preservation periods than the Celsior solution: comparative study for ventricular and coronary endothelial function after 24-h heart preservation

Abstract: The UW group showed better left ventricular function than the Celsior group, indicating that the UW solution has greater potential for long-term preservation than Celsior solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…4, 5 However, many clinicians and researchers are reticent to use such a high potassium solution, particularly with regard to its putative but controversial effect on coronary and pulmonary vascular endothelium. 2, 3, 8 …”
Section: Discussionmentioning
confidence: 99%
“…4, 5 However, many clinicians and researchers are reticent to use such a high potassium solution, particularly with regard to its putative but controversial effect on coronary and pulmonary vascular endothelium. 2, 3, 8 …”
Section: Discussionmentioning
confidence: 99%
“…In an experimental study from Kajihara et al. UW solution led to a better left ventricular function and a greater potential for long‐term preservation [20]. Furthermore, Michel et al.…”
Section: Discussionmentioning
confidence: 99%
“…In an experimental study from Kajihara et al UW solution led to a better left ventricular function and a greater potential for long-term preservation [20]. Furthermore, Michel et al showed in rat hearts that UW resulted in better heart contractility, lower LDH and CK levels during perfusion then HTK [21].…”
Section: Patients Survivalmentioning
confidence: 99%
“…Many of the heart studies have compared one preservation solution with another,26,29–33,35,3944 and with or without additives, such as channel activators or blockers,1,11,4549 exchange inhibitors,5052 anesthetics,2,9,49 nitric oxide (NO) donors,53 perfluorocarbons54 or BDM 1,30,55. For example, Celsior solution preserved function better than ViaSpan in several studies,44,56 whereas others found that ViaSpan was better than Celsior 29,30. HTK was found to be more protective than ViaSpan in one study,43 whereas another found the reverse to be true 26.…”
Section: Discussionmentioning
confidence: 99%